2019
DOI: 10.1093/humupd/dmz041
|View full text |Cite
|
Sign up to set email alerts
|

Do cancer therapies damage the uterus and compromise fertility?

Abstract: BACKGROUND As cancer survival rates improve, understanding and preventing the adverse off-target and long-term impacts of cancer treatments, including impacts on fertility, have become increasingly important. Cancer therapy-mediated damage to the ovary and depletion of the primordial follicle reserve are well characterised. However, our knowledge of the full extent of damage to the rest of the female reproductive tract, in particular the uterus, is limited. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
66
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(68 citation statements)
references
References 80 publications
1
66
0
1
Order By: Relevance
“…AP RT in particular increased the risk of preterm delivery (OR 3.81; CI 2.02–7.19) with 13 out of 72 survivors in this subgroup delivering before 37 weeks ( Madanat-Harjuoja et al , 2010 ). However, it is important to note that while the risk of LBW and prematurity may be partly due to decreased uterine volume as a result of pelvic radiation, other studies have observed these finding for cancers not typically treated with pelvic radiation and among those treated with chemotherapy only, suggesting that other factors may also contribute ( Griffiths et al , 2019 ).…”
Section: Fertility Outcomes Following Rtmentioning
confidence: 99%
See 1 more Smart Citation
“…AP RT in particular increased the risk of preterm delivery (OR 3.81; CI 2.02–7.19) with 13 out of 72 survivors in this subgroup delivering before 37 weeks ( Madanat-Harjuoja et al , 2010 ). However, it is important to note that while the risk of LBW and prematurity may be partly due to decreased uterine volume as a result of pelvic radiation, other studies have observed these finding for cancers not typically treated with pelvic radiation and among those treated with chemotherapy only, suggesting that other factors may also contribute ( Griffiths et al , 2019 ).…”
Section: Fertility Outcomes Following Rtmentioning
confidence: 99%
“…In addition, there is some evidence that chemotherapy (which often accompanies radiation) directly damages the uterus, as summarized in Fig. 1 ( Griffiths et al , 2019 ; van de Loo et al , 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, an earlier study found that exposure to CTX in vivo had adverse effects on oocyte function, and it can be partially reversible. However, pregnancy failure may also be related to uterus- and pregnancy-supporting dysfunction ( Garg et al, 2020 ; Griffiths et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…49 Moreover, damage to the uterine muscles and decreased myometrium volume can be involved in further problems with uterine contractions during labor. 49 Consistently, the study findings indicated a decrease in the size of uterine glands after DOX administration. The uterine glands play a pivotal role in uterine receptivity.…”
Section: Discussionmentioning
confidence: 99%